1996
DOI: 10.1590/s0004-282x1996000100006
|View full text |Cite
|
Sign up to set email alerts
|

Rural or urban living and Parkinson's disease

Abstract: -Although the precise etiology of Parkinson's disease (PD) is as yet unknown, it appears that certain environmental factors are involved. Prior living in a rural area has been implicated as a possible risk factor for PD, particularly in the early onset type. We evaluated the role of previous living conditions in the clinical correlates and outcome characteristics of 118 PD patients. All of them were seen from January 1987 to October 1992. The Rural Group (RG) comprised 71 patients (60.2%) who had lived in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
0
11
0
2
Order By: Relevance
“…Of 13 studies, 6 did not indicate whether they excluded patients developing atypical symptoms during the follow-up period. 5,[7][8][9]11,12 Patients with atypical symptoms may have distinct disorders with distinct prognostic factors, despite early clinical features entirely consistent with PD.…”
Section: Methodologic Variability Across Studiesmentioning
confidence: 99%
“…Of 13 studies, 6 did not indicate whether they excluded patients developing atypical symptoms during the follow-up period. 5,[7][8][9]11,12 Patients with atypical symptoms may have distinct disorders with distinct prognostic factors, despite early clinical features entirely consistent with PD.…”
Section: Methodologic Variability Across Studiesmentioning
confidence: 99%
“…Numerous studies worldwide have identified rural living, farming, gardening and drinking well water as risk factors for PD (Semchuk et al, 1991;Butterfield et al, 1993;Hubble et al, 1993a;Morano et al, 1994;Ferraz et al, 1996;Gorell et al, 1998;Marder et al, 1998;Zorzon et al, 2002;Korell and Tanner, 2005), but the results are somewhat inconsistent because of differences in the way the studies assessed the effects of rural living. Overall, risk of PD appears to be increased in rural dwellers -especially in the USA.…”
Section: Rural Living Farming Well Watermentioning
confidence: 99%
“…Although many PD risk factors have been suggested in epidemiology studies, [1;4;11;21-25] there is very little direct evidence implicating the environment as the primary etiology in the pathophysiology of PD. This manuscript describes clinical features and exposures to previously described PD risk factor exposures in 18 cohabitating unrelated spouses with parkinsonism.…”
Section: Discussionmentioning
confidence: 99%
“…Proposed environmental risk factors for PD include industrialization, rural living, and pesticide or heavy metal exposure. [1-5] Twin studies do not support a genetic cause, especially in older onset subjects. [6;7] Environmental and occupational exposures have been associated with the development of atypical parkinsonism, and may provide clues to the etiology of idiopathic PD.…”
Section: Introductionmentioning
confidence: 99%